Spectrophotometric Assays for Antioxidant Enzymes in Plants - Elavarthi, S.; Martin, B.
Reactive oxygen species (ROS)are formed in biological systems as part of normal metabolism. Adverse environmental factors like drought stress result in increased levels of ROS that are detrimental to the plant (1, 2). To avoid damage caused by these excess ROS, plants have developed elaborate mechanisms to manage them at sustainable levels. Enzymes play an important role in lowering the ROS levels and helping avoid oxidative stress. Superoxide dismutase, catalase, ascorbate peroxidase, and glutathione reductase play a vital role in combating oxidative stress. Measuring these enzyme activities spectrophotometrically provides researchers an easy and precise way to study and understand an important part of the defense against oxidative stress. In this chapter we provide details of the assays we used to determine the enzyme activities spectrophotometrically. Antioxidant enzyme responses to moderate water-deficit stress were studied. All enzyme assays were conducted using wheat leaf tissue.
Keywords: ANTIOXIDANT ENZYMES; ASCORBATE PEROXIDASE; CATALASE; GLUTATHIONE REDUCTASE; OXIDATIVE STRESS; SUPEROXIDE DISMUTASE